Intravenous verses oral iron supplementation for anaemia of pregnancy in the arid region of Western India: a retrospective cohort study - Jain, Yogesh K.; Joshi, Nitin K.; Shah, Kalpana R.; Chittora, Isha; Joshi, Vibha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: India has a high prevalence of anemia in pregnant females, resulting greater risk of blood transfusion and its associated complications during the peripartum period. Administration of intravenous iron sucrose may reduce such a risk. Due to a greater prevalence in western arid region of India, this study was planned to compare efficacy and safety of intravenous iron sucrose and oral ferrous ascorbate in the treatment of iron deficiency anemia of pregnancy in a community health center of rural Jodhpur. Methods: A retrospective cohort study was conducted in Community Health Center of Jodhpur to review the heamoglobin values of pregnant females in 28 to 37 weeks of gestation, treated with either intravenous iron sucrose or oral iron ascorbate. Cohorts were matched based on parity and age, and the hemoglobin values after 2, 4 and 6 weeks of start of therapy were compared using independent t-test. Results: Of the 152 pregnant females’ records included in the study, 82 were provided intravenous therapy and 70 were given oral iron therapy. Both the modes of administration showed marked increase in heamoglobin values, with statistically more significant rise through parenteral route at each point of measurement. Overall change in mean heamoglobin was 2.43 g/dl through iv route and 0.61 g/dl through oral route (p<0.001). Adverse events following therapy were reported by 9 females from intravenous group and 31 women from oral group. Conclusions: The study provided evidence that parenterally administered iron sucrose elevated hemoglobin and restored iron stores better than oral ferrous ascorbate with lesser adverse reactions.